Program “KOMPAK” untuk Meningkatkan Kualitas Hidup Ibu Pasien Kanker Anak - Anak Agung Ayu Ratna Paramita; Sofia Retnowati (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2019)
Cancer in children affects not only the patient but for the parents. Parents who have a child with cancer, experience psychological burdens manifested in confusion, shock, rejection, exhaustion, anxiety, and worry. If not handled properly, these symptoms will make them experience stress. It can affect their health quality of life and reduce their ability to accompany child with cancer. Whereas parents health condition greatly affect the health condition of patients with cancer. This study aimed to improve the quality of life of parents who have a child with cancer by providing "KOMPAK" program. Participants from this study were 5 mothers of child with cancer. The research method used the one group pretest-posttest design. The analysis used Wilcoxon signed-rank non-parametric test. Results showed that there was a significant improvement in the quality of life in mothers of children with cancer Z = -2.023 and p = 0.043 ( p < 0.05). These results showed that "KOMPAK" program could improve their quality of life.